2011
DOI: 10.1103/physrevd.84.122003
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of LISA pathfinder test-mass noise

Abstract: LISA Pathfinder (LPF) is a mission aiming to test the critical technology for the forthcoming space-based gravitational wave detectors. The main scientific objective of the LPF mission is to demonstrate test-masses free-falling with residual accelerations below 3 × 10 −14 m s −2 / √ Hz at 1 mHz. Reaching such an ambitious target will require a significant amount of system optimisation and characterisation, which will in turn require accurate and quantitative noise analysis procedures. In this paper we discuss … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…It is worth noticing here that the allowed range of discrepancy in the parameters is orders of magnitude higher than the expected uncertainty in the parameters. Indeed, previous studies [8,12,20,24,30] have shown that the order of magnitude of expected error on the parameters considered in our analysis is σ G df σ G lfs 10 −5 for the control gains, σ ω 2 1 σ ω 2 2 10 −10 s −2 for the stiffnesses and σ S21 10 −8 for the sensing cross-coupling.…”
Section: Robustness Analysismentioning
confidence: 80%
See 2 more Smart Citations
“…It is worth noticing here that the allowed range of discrepancy in the parameters is orders of magnitude higher than the expected uncertainty in the parameters. Indeed, previous studies [8,12,20,24,30] have shown that the order of magnitude of expected error on the parameters considered in our analysis is σ G df σ G lfs 10 −5 for the control gains, σ ω 2 1 σ ω 2 2 10 −10 s −2 for the stiffnesses and σ S21 10 −8 for the sensing cross-coupling.…”
Section: Robustness Analysismentioning
confidence: 80%
“…We are now prepared to compare the results obtained analytically with the prediction of the numerical algorithm based on the dispersion function -Eq. (12). To do so we inject a white noise data stream to the input channel under consideration, which for the analysis of the F 2121 term is the drag-free channel.…”
Section: Single Tone Input: Undetermined Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the analysis of noise is typically performed in the frequency or time-frequency domain therefore we aim to develop a noise analysis tool that is suited for such data. The problem of the statistical analysis of noise in the frequency domain was already formulated in [7] where a number of data analysis strategies were developed and compared. In this paper we present a further refinement of the Kolmogorov-Smirnov test presented in [7] and we extend its range of application to the time-frequency domain.…”
Section: Introductionmentioning
confidence: 99%
“…The problem of the statistical analysis of noise in the frequency domain was already formulated in [7] where a number of data analysis strategies were developed and compared. In this paper we present a further refinement of the Kolmogorov-Smirnov test presented in [7] and we extend its range of application to the time-frequency domain. The analysis of time-frequency data is particularly interesting since it allows to identify and characterize non-stationary noise.…”
Section: Introductionmentioning
confidence: 99%